Oscillatory Adaptive Yaw-Plane Control of Biorobotic Autonomous Underwater Vehicles Using Pectoral-Like Fins - Mugdha S. Naik; Sahjendra N. Singh (Applied Bionics and Biomechanics)
This article considers the control of a biorobotic autonomous underwater vehicle (BAUV) in the yaw plane using biologically inspired oscillatory pectoral-like fins of marine animals. The fins are assumed to be oscillating harmonically with a combined linear (sway) and angular (yaw) motion producing unsteady forces, which are used for fish-like control of BAUVs. Manoeuvring of the BAUV in the yaw plane is accomplished by altering the bias (mean) angle of the angular motion of the fin. For the derivation of the adaptive control system, it is assumed that the physical parameters, the hydrodynamic coefficients, and the fin force and moment are not known. A direct adaptive sampled-data control system for the trajectory control of the yaw-angle using only yaw-angle measurement is derived. The parameter adaptation law is based on the normalised gradient scheme. Simulation results for the set point control, sinusoidal trajectory tracking and turning manoeuvres are presented, which show that the control system accomplishes precise trajectory control in spite of the parameter uncertainties.